2016
DOI: 10.1523/jneurosci.2546-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Evidence for Alternative Motor Networks in REM Sleep Behavior Disorder

Abstract: Patients with Parkinson's disease (PD) and REM sleep behavior disorder (RBD) show mostly unimpaired motor behavior during REM sleep, which contrasts strongly to coexistent nocturnal bradykinesia. The reason for this sudden amelioration of motor control in REM sleep is unknown, however. We set out to determine whether movements during REM sleep are processed by different motor networks than movements in the waking state. We recorded local field potentials in the subthalamic nucleus (STN) and scalp EEG (modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
1
18
1
Order By: Relevance
“…It was first reported by Urrestarazu et al [13] (2009) that beta oscillations in the STN of PD patients decreased in non-REM sleep and recovered in REM sleep. The modulation of beta oscillation during movements in REM sleep was shown to be different with that during wakefulness [35], [42]. It was also suggested by Thompson et al [14] (2017) that all frequency bands were significantly different between sleep stages.…”
Section: Discussionmentioning
confidence: 99%
“…It was first reported by Urrestarazu et al [13] (2009) that beta oscillations in the STN of PD patients decreased in non-REM sleep and recovered in REM sleep. The modulation of beta oscillation during movements in REM sleep was shown to be different with that during wakefulness [35], [42]. It was also suggested by Thompson et al [14] (2017) that all frequency bands were significantly different between sleep stages.…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that half of patients with REM sleep behaviour disorder (RBD) smiled, although that only some controls did. Indeed, recent studies have suggested that during RBD, unlike what happens when awake, muscle activation is driven by the motor cortex and bypasses the basal ganglia (Arnulf, 2012; Hackius, Werth, Surucu, Baumann, & Imbach, 2016; Mayer, Bitterlich, Kuwert, Ritt, & Stefan, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This result supports previous works suggesting that the motor signature of RBD is the same across disorders (Oudiette et al., ), and that movements and facial expressions are produced by different networks when asleep to when awake (Arnulf, ). Several lines of evidence (provided by movement analysis, functional imaging and deep brain recordings) suggest that during RBD, the activation of muscles is driven by the motor cortex and bypasses the basal ganglia (De Cock et al., ; Hackius, Werth, Surucu, Baumann, & Imbach, ; Mayer, Bitterlich, Kuwert, Ritt, & Stefan, ).…”
Section: Discussionmentioning
confidence: 99%